Selection of potential bacterial probiotics for tiger grouper (Epinephelus fuscoguttatus forsskal) larviculture - Al-Saari, Nurhidayu (2012)
Rapid development in today’s aquaculture industries have expanded to the level of commercial scale and has indirectly led to environmental degradation and catastrophic losses due to bacterial diseases. Thus, the application of probiotics was proposed as an environmental-friendly preventive measure. This study was carried out specifically to search for probiotic candidates for use in the larviculture of Epinephelus fuscoguttatus. Hypothetically, selected intestinal microfloras of E. fuscoguttatus are able to confer protection on larvae by exhibiting antagonistic activity against pathogenic bacteria. A set of criteria for bacterial probiotics was used in this study, focusing on phenotypic and genotypic characterizations of the candidate strains, in vitro capacity to inhibit the growth of targeted competitive strains, the haemolytic activity and antibiotic susceptibility of selected candidates and virulence assessment to the host. Initially, the intestines of healthy individual grouper which were randomly collected from three geographically distant farms in Malaysia were processed and bacterial isolation was performed. A preliminary identification and grouping method successfully identified 31 species, while 22 isolates as unidentified from a total of 123 isolated aerobes and facultative anaerobes. The first screening process was undertaken to assess the antagonistic activity exhibited by the isolates against four common fish pathogens. Of the 123 isolates, 40 (32.5%) displayed strong antagonistic activity, mostly Gram-positive bacteria (n=32; 80%). The haemolytic nature of the short listed probionts was then assessed where only nine (22.5%) showed no breakdown of red blood cells and they were grouped into five genera based on 16S rRNA gene sequence analysis. This genotypic strategy was used to eliminate another four isolates considering their potential pathogenic nature to human and sequences similarity from which they were considered identical. Screening process was ended with the antibiotic susceptibility assay of five selected isolates which resulted in the elimination of V. harveyi i.e. JAQ01 and JAQ02 due to their opportunistic nature and the availability of incomprehensible evidence that these strains maympotentially carry resistance genes for β-lactamase in a transferrable genetic material.Considering the needs for an advanced study to measure the antagonism capacity of three selected candidates, bacteriocin-like inhibitory substances (BLIS) and co-culture assays were performed. The former assay nominated Bacillus cereus JAQ04 as the most promising candidates with initial addition at 108 and/or 109 cfu/mL with 48 and/or 72 h pre-incubation time. Alternatively, for co-culture method, the growth of pathogenic V. alginolyticus can also be inhibited at 105 cfu/mL of all probionts tested. Both methods revealed that the highest inhibition of pathogens has always associated with the introduction of significantly higher densities of probionts. Lastly, virulence assessment was made by determining the relationship observed between the probiont concentrations with larval survival. Conclusively, in relation to the previous antagonistic assay, 105 cfu/mL of B. cereus (JAQ04) and Micrococcus luteus (JAQ07) were recommended as the safest and adequate initial amount for use in field trial. Both bacteria needed at least 48 h to proliferate before being able to counteract the pathogens. Thorough studies on these bacteria including in-depth assessment on their effect in vivo are recommended.